2011
DOI: 10.1258/ebm.2010.010179
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B x-interacting protein induces HepG2 cell proliferation through activation of the phosphatidylinositol 3-kinase/Akt pathway

Abstract: Hepatitis B x-interacting protein (HBXIP), a co-factor of survivin, was originally identified by its binding with the C-terminus of the hepatitis B virus x protein (HBx). We have recently shown that HBXIP promotes the growth of both normal liver cells and hepatoma cells in vitro, but the molecular mechanisms of this have not been documented. In this study, we investigated the potential effects of HBXIP on the proliferation of HepG2 cells and the intracellular signaling pathway mediating these changes. Over-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…It has been reported that S100A4 expression can be enhanced by AKT kinase in breast cancer cell lines (29) and HBXIP is able to active AKT signaling in hepatoma HepG2 cells (30). Thus, we supposed that PI3K/AKT pathway may be involved in the regulation of S100A4 meditated by HBXIP in breast cancer cells.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…It has been reported that S100A4 expression can be enhanced by AKT kinase in breast cancer cell lines (29) and HBXIP is able to active AKT signaling in hepatoma HepG2 cells (30). Thus, we supposed that PI3K/AKT pathway may be involved in the regulation of S100A4 meditated by HBXIP in breast cancer cells.…”
Section: Resultsmentioning
confidence: 76%
“…It has been reported that the up-regulation of S100A4 involves PI3K/AKT signaling pathway which promotes the proliferation and growth of cancer cells (29). HBXIP was able to active AKT signaling in HepG2 cells (30). Accordingly, we proposed the possibility that HBXIP might upregulate S100A4 through PI3K/AKT signaling pathway as well.…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, both of PKC and MAPK are required for phosphorylation of HBx, which, in turn, alters its subcellular localization and dysregulation of cell cycle progression, leading to hepatocarcinogenesis in HBV-infected cells. Besides, phosphoinositide 3-kinase (PI3K), a family of enzymes linked to extraordinarily diverse group of cellular functions, are involved in cancer (Lee et al, 2001;Yun et al, 2004, Wang et al, 2011. In HBV-infected cells, PI3K/Akt pathway can be activated through Akt phosphorylation by HBXIP, which also induce up-regulate cyclin D and down-regulate p21 and p53 expression, promoting cell proliferation (Wang, et al, 2011).…”
Section: The Roles Of Centrosome In Signaling Pathway In Hbv-induced Hccmentioning
confidence: 99%
“…Chung et al [26] also showed that the HBx contributes to the transcriptional regulation of matrix metallopeptidase 9 through the ERK and PI3K-Akt/ PKB pathway, and increases the invasive potential of cells. In addition, the proliferation of HepG2 cells promoted by hepatitis B X-interacting protein (HBXIP) is associated with activation of the PI3K/Akt signaling pathway [27].…”
Section: Pi3k-akt-bad Signaling Pathwaymentioning
confidence: 99%